Impacts of market impact cost on portfolio selection strategies - Tang, Jingxiang (Nanyang Technological University, 2021)
This report studies optimal dynamic portfolio choice with mean-variance analysis in continuous time when there are market impact costs. The optimal policy is hard to characterize, so instead we solved a tractable alternative dynamic portfolio choice problem for a sub-optimal policy. The alternative dynamic portfolio choice problem captures market impact cost in the objective instead of the price dynamics.